Durasian (Pre) Occupations - Higgins, Lynn A. (L' esprit créateur, 1990)
Durasian (Pre)Occupations Lynn A. Higgins M ARGUERITE DURAS’S WRITING is haunted by the cinema. From the sound of the sea and the colors of the sunset reflected on a child’s face in Moderato Cantabile (1958) through the de scription of the ball at S. Thalia where Loi V. Stein lost her fiancé and her mind, there is a hallucinatory attention to visual mise-en-scène. Pro tagonists are obsessed by visualized scenes: as Loi watches/imagines the lovemaking between Jacques Hold and Tatiana Karl, she stages a drama of spectatorship1; similarly, the French Woman in Hiroshima mon amour (1959) examines her own role as spectator as she claims " J’ai tout vu," when what she has seen is a documentary film in a museum. Cinema has thematic importance, too, at least as early as the 1950 novel, Un Barrage contre le pacifique (where the mother plays piano accom paniment for silent films at the " Eden Cinema" ) and as recently as La Douleur (1985), in which both a torturer and her victim imagine them selves at the cinema. It was only a small leap when Duras moved into filmmaking. A sense of the continuity of the œuvre was summarized by Hélène Cixous in her suggestion that there is a Durasian " fantasme fondamen tal." 2Echoes of that fantasm reverberate from Duras’s novels through her cinematic production, including Hiroshima mon amour, the film she made together with Alain Resnais. While acknowledging that the film is a collaborative effort, my project here is to examine Hiroshima in the context of Duras’s novels, tracing in particular her representations of the Second World War. I will read the film forward to La Douleur, where the war reemerges as a major theme after a 25-year hiatus. But first, and more perversely, I will read the film backward as an adaptation of Moderato Cantabile,3a novel in which the war makes no appearance at all. Reading from film to book will make it possible to understand the role of the war both as itself and as sign of a Durasian " fantasme." Perhaps it was the cinematic quality of her writing that encouraged Resnais to seek Duras’s help. Associated with " the Nouvelle Vague" to the extent that his films are extremely " literary," Resnais has turned for scripts to such well-known figures as Jean Cayrol (for Nuit et Brouillard and Muriel), Raymond Queneau (for Le Chant du Styrène), and Alain Vol. XXX, No. 2 47 L ’E sprit C réateur Robbe-Grillet (L ’Année dernière à Marienbad). Hiroshima mon amour is thus the encounter of the cinematic writer and the literary filmmaker, the collaboration of " écriture filmique" and "caméra stylo." Madeleine Borgomano suggests that perhaps, in addition, there was a " rencontre de fantasmes." 4 There was also a " rencontre" of coincidences. In mid-1958, Resnais’s current project was stalled; he had been commissioned to make a FrancoJapanese documentary about the consequences of nuclear weaponry, but had concluded that the subject was too vast, and that, in any case, there were already plenty of documentaries about the bomb. At the same time, he had been eager to make a poetic film which he conceived in abstract terms as " l’idée de deux histoires qui s’imbriqueraient, l’une dans l’autre, et qui seraient toutes deux racontées au présent." 5Having read the just-published Moderato Cantabile, Resnais almost jokingly sug gested that if Duras would consent to work with him, he might transform his project into a fiction film. At the same time, financing was offered by a Japanese producer, on the condition that half the shooting would take place in Japan, and that the film would include Japanese actors. The result was Hiroshima mon amour, described by Resnais as " une histoire d’amour—dans ma tête c’était un peu une espèce de Moderato Cantabile —mais d’où l’angoisse atomique ne serait pas absente." 6Duras, for her part, reiterates this curious palimpsest of fiction and history in her state ment that it is " Impossible de parler de Hiroshima. Tout ce qu’on peut faire c’est de parler...